Effet et faisabilité d'un programme de réhabilitation non conventionnel chez des sujets atteints de bronchopneumopathie chronique obstructive : étude quasi-expérimentale à Laghouat. - FATMI Hanane Meriem; ZENIKHERI Aicha; LAGRAA Lyna (université ammar telidji laghouat, 2025)
Pulmonary rehabilitation (PR) programs face significant challenges related to limited healthcare access and poor adherence, particularly in resource-constrained settings such as Algeria. This study aimed to evaluate the feasibility and efficacy of a simplified PR protocol, incorporating functional exercises based on repeated Set of floor lifts (SLS), tailored to the cultural and physical capabilities of patients with chronic obstructive pulmonary disease (COPD). A prospective interventional study targeting 15 COPD patients with muscle dysfunction was conducted over 63 days in the pneumology department of Ali Ben Deghine Hospital, Laghouat. Patients were enrolled and followed through structured assessments at baseline and post-intervention. Adherence rates and clinical outcomes, including dyspnea scores (mMRC, CAT), functional mobility (Timed Up and Go test), six-minute walk test (6MWT), and isometric muscle strength and endurance, were evaluated. The adherence rate to the protocol was 46.67%. Among adherent patients, there was a statistically significant reduction in dyspnea severity (median mMRC = 2.00 [1.00–2.50], p = 0.011) and CAT scores (median final score 9.00 vs. 18.50 in non-adherents, p = 0.009), accompanied by improved sleep quality and daily activity levels. Improvements in TUG and STS suggest a positive functional response within clinically relevant margins MCID. Although both groups exhibited a decline in 6MWT distance, adherent patients better preserved their walking capacity (p = 0.728). Muscle strength assessments revealed superior isometric knee flexion strength (p = 0.043) and knee extension endurance (p = 0.028) in adherents. This simplified PR protocol demonstrates feasibility and clinical benefits in a low-resource setting, highlighting the importance of culturally and contextually adapted rehabilitation strategies for COPD management. Further studies are necessary to optimize protocol parameters and assess long-term outcomes.
CD-ROM